An Unusual Presentation of Rhabdomyolysis in a Newly Diagnosed Sjögren’s Syndrome Associated Polymyositis - Shanti VIRUPANNAVAR; Suncica VOLKOV (Archives of Rheumatology, 2016)
Rhabdomyolysis is a serious and potentially life-threatening syndrome due to rapid breakdown of skeletal muscle fibers. Acquired and genetic causes should be investigated when patients present with rhabdomyolysis. In this article, we report a patient of polymyositis associated with Sjögren’s syndrome, inducing rhabdomyolysis.